Surface settlement induced by tunneling in greenfield condition through physical modelling - Marto, Aminaton (Penerbit UTM Press, 2015)
Geotechnical conditions such as tunnel dimensions, tunneling method and soil type are few factors influencing the ground movement or disturbance. This paper presents the effect of tunnel cover to diameter ratio and relative density of sand on surface settlement induced by tunneling using physical modelling. The aluminum casing with outer diameter of 50 mm was used to model the tunnel shield. The size of the casing was 2 mm diameter larger than the tunnel lining. The tunnel excavation was done by pulling out the tunnel shield at constant speed with a mechanical pulley. The tested variables are cover to diameter ratio (1, 2 and 3) and relative density of sand (30%, 50% and 75%). The results demonstrated that the surface settlement decreased as the relative density increased. Also, as the relative density of sand increased, the overload factor at collapse increased. The surface settlement was at the highest when the cover to diameter ratio was 2. It can be concluded that in greenfield condition, the relative density and cover to diameter ratio affect the surface settlement.